I agree Our site saves small pieces of text information (cookies) on your device in order to deliver better content and for statistical purposes. You can disable the usage of cookies by changing the settings of your browser. By browsing our website without changing the browser settings you grant us permission to store that information on your device.

Download Files
### Definitions File

### Template File

### Check File

theory Defs imports Main begin text ‹Definitions and lemmas from the tutorial› fun snoc :: "'a list ⇒ 'a ⇒ 'a list" where "snoc [] x = [x]" | "snoc (y # ys) x = y # (snoc ys x)" fun reverse :: "'a list ⇒ 'a list" where "reverse [] = []" | "reverse (x # xs) = snoc (reverse xs) x" lemma reverse_snoc: "reverse (snoc xs y) = y # reverse xs" by (induct xs) auto theorem reverse_reverse: "reverse (reverse xs) = xs" by (induct xs) (auto simp add: reverse_snoc) end

theory Submission imports Defs begin fun list_sum :: "nat list ⇒ nat" where "list_sum _ = undefined" theorem list_sum_reverse: "list_sum (reverse xs) = list_sum xs" sorry fun upto :: "nat ⇒ nat list" where "upto _ = undefined" theorem gauss: "list_sum (upto n) = n * (n + 1) div 2" sorry end

theory Check imports Submission begin theorem list_sum_reverse: "list_sum (reverse xs) = list_sum xs" by (rule Submission.list_sum_reverse) theorem gauss: "list_sum (upto n) = n * (n + 1) div 2" by (rule Submission.gauss) end

Terms and Conditions